Risk aversion in experiments - Cox, James C., Ph. D.; Harrison, Glenn W. (Research in experimental economics ;, 2008)
This series presents research utilizing laboratory experimental methods in economics. A distinction between this book series and traditional journals is that the book series format allows for papers and features that might not be appropriate for journals. Some examples which have been included in this series are: papers with complete presentation of experimental instructions and data, papers which report replication and robustness results, methodological papers, and theoretical papers motivated specifically by experimentation. The series currently consists of two different types of volumes. Some volumes are open-submission covering all topics. The papers in these volumes are reviewed externally. The other volumes, recently undertaken and with Prof. Charles Holt as a co-editor, are focused on a single, broad research topic with papers solicited and reviewed by the co-editors.